Iodine‐131‐meta‐iodobenzylguanidine therapy for patients with newly diagnosed high‐risk neuroblastoma - Kraal, Kathelijne CJM (Cochrane Database Syst Rev, 2017)
BACKGROUND: Patients with newly diagnosed high‐risk (HR) neuroblastoma (NBL) still have a poor outcome, despite multi‐modality intensive therapy. This poor outcome necessitates the search for new therapies, such as treatment with (131)I‐meta‐iodobenzylguanidine ((131)I‐MIBG). OBJECTIVES: To assess the efficacy and adverse effects of (131)I‐MIBG therapy in patients with newly diagnosed HR NBL. SEARCH METHODS: We searched the following electronic databases: the Cochrane Central Register of Controlled Trials (CENTRAL; the Cochrane Library 2016, Issue 3), MEDLINE (PubMed) (1945 to 25 April 2016) and Embase (Ovid) (1980 to 25 April 2016). In addition, we handsearched reference lists of relevant articles and reviews. We also assessed the conference proceedings of the International Society for Paediatric Oncology, Advances in Neuroblastoma Research and the American Society of Clinical Oncology; all from 2010 up to and including 2015. We scanned the International Standard Randomized Controlled Trial Number (ISRCTN) Register (www.isrctn.com) and the National Institutes of Health Register for ongoing trials (www.clinicaltrials.gov) on 13 April 2016. SELECTION CRITERIA: Randomised controlled trials (RCTs), controlled clinical trials (CCTs), non‐randomised single‐arm trials with historical controls and cohort studies examining the efficacy of (131)I‐MIBG therapy in 10 or more patients with newly diagnosed HR NBL. DATA COLLECTION AND ANALYSIS: Two review authors independently performed the study selection, risk of bias assessment and data extraction. MAIN RESULTS: We identified two eligible cohort studies including 60 children with newly diagnosed HR NBL. All studies had methodological limitations, with regard to both internal (risk of bias) and external validity. As the studies were not comparable with regard to prognostic factors and treatment (and often used different outcome definitions), pooling of results was not possible. In one study, the objective response rate (ORR) was 73% after surgery; the median overall survival was 15 months (95% confidence interval (CI) 7 to 23); five‐year overall survival was 14.6%; median event‐free survival was 10 months (95% CI 7 to 13); and five‐year event‐free survival was 12.2%. In the other study, the ORR was 56% after myeloablative therapy and autologous stem cell transplantation; 10‐year overall survival was 6.25%; and event‐free survival was not reported. With regard to short‐term adverse effects, one study showed a prevalence of 2% (95% CI 0% to 13%; best‐case scenario) for death due to myelosuppression. After the first cycle of (131)I‐MIBG therapy in one study, platelet toxicity occurred in 38% (95% CI 18% to 61%), neutrophil toxicity in 50% (95% CI 28% to 72%) and haemoglobin toxicity in 69% (95% CI 44% to 86%); after the second cycle this was 60% (95% CI 36% to 80%) for platelets and neutrophils and 53% (95% CI 30% to 75%) for haemoglobin. In one study, the prevalence of hepatic toxicity during or within four weeks after last the MIBG treatment was 0% (95% CI 0% to 9%; best‐case scenario). Neither study reported cardiovascular toxicity and sialoadenitis. One study assessed long‐term adverse events in some of the children: there was elevated plasma thyroid‐stimulating hormone in 45% (95% CI 27% to 65%) of children; in all children, free T4 was within the age‐related normal range (0%, 95% CI 0% to 15%). There were no secondary malignancies observed (0%, 95% CI 0% to 9%), but only five children survived more than four years. AUTHORS' CONCLUSIONS: We identified no RCTs or CCTs comparing the effectiveness of treatment including (131)I‐MIBG therapy versus treatment not including (131)I‐MIBG therapy in patients with newly diagnosed HR NBL. We found two small observational studies including chilren. They had high risk of bias, and not all relevant outcome results were available. Based on the currently available evidence, we cannot make recommendations for the use of (131)I‐MIBG therapy in patients with newly diagnosed HR NBL in clinical practice. More high‐quality research is needed.